2016
DOI: 10.1680/jstbu.15.00130
|View full text |Cite
|
Sign up to set email alerts
|

Using fibres and fly ash in concrete-filled steel tube columns

Abstract: The aim of the present study is to experimentally investigate the behaviour of concrete-filled steel tubular columns under axial loading. The grade of concrete used is M20 and the yield strength of the steel is 250 MPa. Fly ash is used as partial replacement (25%) of cement and 0·5, 1·0 and 1·5% polypropylene fibres are added to the concrete; the optimum mix is selected based on the mechanical properties of the concrete and used as a filler material for the columns. Twenty-seven columns of different cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…CFST sections, which are constructed from produced steel tube sections and concrete filling, have been widely used as a vertical bearing component. The main advantages offered by CFST include increased strength, ductility, significant cost savings, fire resistance, and quick installation due to the fact that the CFST column does not require the use of a reinforced cage or formwork [10][11][12][13][14]. The stability of the steel tube is enhanced by the concrete inside it.…”
Section: Introductionmentioning
confidence: 99%
“…CFST sections, which are constructed from produced steel tube sections and concrete filling, have been widely used as a vertical bearing component. The main advantages offered by CFST include increased strength, ductility, significant cost savings, fire resistance, and quick installation due to the fact that the CFST column does not require the use of a reinforced cage or formwork [10][11][12][13][14]. The stability of the steel tube is enhanced by the concrete inside it.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed buckling moment equation showed that a sweep equal to the girder sweep tolerance of the Precast/Prestressed Concrete Institute manual corresponds to a reduction of about 35% in the buckling moment compared to the perfect configuration of the beam. Overall, the present study provides reasonable approaches for estimating the buckling moments of RC beams, in particular, with geometrical imperfections and concrete cracking.The next paper (Sankar Jegadesh and Jayalekshmi, 2016) tested the axial behaviour of CFST columns with different cross-sections (circular, square, and rectangular types) and two different concrete infills produced using fly ash as partial replacement (25%) of cement and 0·5-1·5% polypropylene fibres. A comparative study was also made between the experimental strength and theoretical values obtained from various international design codes.…”
mentioning
confidence: 99%
“…The next paper (Sankar Jegadesh and Jayalekshmi, 2016) tested the axial behaviour of CFST columns with different cross-sections (circular, square, and rectangular types) and two different concrete infills produced using fly ash as partial replacement (25%) of cement and 0·5-1·5% polypropylene fibres. A comparative study was also made between the experimental strength and theoretical values obtained from various international design codes.…”
mentioning
confidence: 99%